On genetic and evolution algebras in dimension three - Mukhamedov, Farrukh; Qaralleh, Izzat; Pirnapasov , Abror (Hikari Ltd, 2016)
In mathematical genetics genetic algebras are devoted to describe some model in genetics. The genetic algebra usually has a basis corresponding to genetically different gametes, and the structure constant of the algebra used to encode the probabilities of producing offspring of several types. In this paper, we find the connection between the genetic and evolution algebras in dimension three